2021
DOI: 10.1186/s13048-021-00835-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of synchronous serous ovarian cancer and uterine serous endometrial intraepithelial carcinoma

Abstract: Background Serous endometrial intraepithelial carcinoma (SEIC) is now considered to represent an early stage of uterine serous carcinoma (USC). It is an intraepithelial lesion but has been reported to cause extrauterine metastases. We report a case of SEIC with serous ovarian carcinoma and lymph node metastasis. Case presentation A 57-year-old post-menopausal woman (gravida 3, para 2, SA1) was referred to our hospital with lower abdominal pain. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In 46 of 81 patients, there was no evidence of disease at the end of follow-up, 12 patients were alive with the disease, 18 patients died from the disease and 2 patients died from other causes. In two studies, 62.5% and 33.3% of patients receiving adjuvant chemotherapy, respectively, relapsed [2,10], while, in three studies, none of the patients relapsed [3,12,14]. Among patients not receiving any adjuvant treatment, only in one study were no relapses reported [13], and the average recurrence rate was 28.78%, ranging from 16.6% to 100%, and the DFS was 59.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 46 of 81 patients, there was no evidence of disease at the end of follow-up, 12 patients were alive with the disease, 18 patients died from the disease and 2 patients died from other causes. In two studies, 62.5% and 33.3% of patients receiving adjuvant chemotherapy, respectively, relapsed [2,10], while, in three studies, none of the patients relapsed [3,12,14]. Among patients not receiving any adjuvant treatment, only in one study were no relapses reported [13], and the average recurrence rate was 28.78%, ranging from 16.6% to 100%, and the DFS was 59.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have described simultaneous SEIC and ovarian carcinoma. It was impossible to determine whether these were two independent neoplasms or if the SEIC had developed previously [2,14]. Serous endometrial and ovarian tumors may have similar characteristics under the microscope and may be difficult to distinguish because of their structure alone.…”
Section: Discussionmentioning
confidence: 99%
“…Our study observed SEIC in both pure and mixed USC groups (20% vs. 6.9%), with up to 67% of SEIC patients having extrauterine disease, indicating the aggressive biological behavior of USC and SEIC. As a p53-driven neoplasm, p53 abnormalities exist even in SEIC lesions [ 16 ]. Our study showed that the TP53 mutation rate of p-USC and m-USC groups was 89.3% and 87.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is a major clinical problem for gynecologists, as its diagnosis is very complicated and is based primarily on histopathological criteria [9,10,2]. It is important to distinguish between double primary cancer, or synchronous cancer, and metastatic disease as this helps establish an accurate diagnosis and assess the grade of the tumor and is also essential in selecting optimal follow-up treatment and predicting the patient's prognosis [11,12].…”
Section: Introduction 50mentioning
confidence: 99%